Understanding the Trend and Distribution of Antimicrobial Resistance Using Event Based Surveillance System: EpiWatch - Princy Poovanna Natolanda; Aye Moa; Chandini Raina Macintyre (University of New South Wales, 2020)
Anti-Microbial Resistance (AMR) is a significant public health threat in many countries around the world, endangering the control of infections and infectious disease. AMR related illness has been responsible for annual global mortality of 700,000. Besides health outcomes, they bear an adverse impact on economic development. However, the lack of comprehensive global AMR surveillance data and an over-reliance on indicator-based surveillance system has limited the early detection of emerging AMR threats and trends. Methods; EpiWATCH outbreak database has been used to retrieve AMR outbreak reports between August 2016-March 2020 using keywords such as resistance, resistant, superbug, bugs, MRSA and VRE. Cases were grouped according to geolocation and time to conduct a descriptive epidemiologic analysis of the outbreak. Results; A total of 60 reports on AMR outbreak were detected. Majority of the infections were caused by gram-negative bacteria. Drug-resistant Klebsiella. Acinetobacter and New Delhi Metallo-β-lactamase-1 (NDM-1) Carbapenemase-producing Enterobacteriaceae acquired in hospitals were strongly associated with mortality. As dense places, schools and universities were at-risk locations in the community for Methicillin-resistant Staphylococcus Aureus (MRSA) outbreaks and in hospital settings, the Neonatal units were at risk. Conclusion; EpiWATCH detected AMR outbreaks quickly and timely compared to an indicator-based surveillance system. It detected outbreaks by pathogens not monitored by the World Health Organisation. Also, it presented information on both colonised and infected cases from the population. Thus, EpiWATCH could be complemented with an indicator-based surveillance system for strengthening surveillance and identifying action areas.